Optimal recovery from the making weight process for wrestlers - Ööpik, V. (International Journal of Wrestling Science, 2013)
Depending on the duration, distinction is made between rapid (i.e. within 24-72h), moderate (from 72h to several weeks) and gradual (from several weeks to months) bodyweight reduction. Rapid and moderate bodyweight loss by approximately 5% or more may impair physical performance capacity in well-trained wrestlers. Research data suggest that high carbohydrate intake as well as creatine supplementation with concomitant glucose ingestion promotes recovery of physical performance after rapid/moderate bodyweight loss. Recovery of fluids lost due to dehydration may take 24-48 hours, i.e. much longer than is commonly appreciated by athletes and coaches. Therefore, athletes who have less than 24 hours for recovery after weight loss should not lose more than 2% of their bodyweight through dehydration. Rehydration occurs more rapidly if fluids consumed contain electrolytes, primarily sodium. Dietary sodium citrate supplementation during recovery after rapid bodyweight loss increases blood buffering capacity and plasma volume and stimulates bodyweight regain in trained wrestlers.